Halimane and labdane diterpenoids from Leonurus japonicus and their anti-inflammatory activity. (April 2020) - Li, Hang-Ying; Li, Ya; Wei, Wen-Jun; Ma, Kai-Liang; Chen, Jian-Jun; Gao, Kun
Abstract: Ten highly oxygenated diterpenoids (nine undescribed ones) were isolated from the aerial parts of Leonurus japonicus Houtt. 14, 15-Dinor-labd-5, 8-dien-3, 13-dione was a 14, 15-dinor-labdane diterpenoid possessing a C18 skeleton. 7 β, 9 α -Dihydroxy-6-oxo-labd-13-en-15, 16-amide represented a rare example of labdane diterpenoid featuring an α, β- unsaturated -γ- lactam moiety. The structures of all compounds were elucidated using spectroscopic data analyses and comparisons. The effects of these obtained compounds on nitric oxide (NO) production induced by lipopolysaccharide (LPS) in RAW 264.7 cells were evaluated.(10 R*, 13 R *, 15 R *)-15, 16-Epoxy-6, 13-dihydroxy-15-methoxy-labda-5, 8-dien-7-one inhibited NO production with an IC50 value of 40.1  μ M. Graphical abstract: Diterpenoids from the aerial parts of Leonurus japonicus Houtt., collected in Gansu Province, China. Image 1 Highlights: The aerial parts of Leonurus japonicus afforded nine undescribed highly oxygenated diterpenoids. Compound 8 was a 14, 15-dinor-labdane diterpenoid possessing a C18 skeleton. Compound 10 represented a rare example of labdane diterpenoid featuring an α, β- unsaturated -γ- lactam moiety. Compound 5 showed anti-inflammatory activity with an IC50 value of 40.1  μ M.